PENDEKATAN DIAGNOSA ENDOCARDITIS PADA ANJING MINI POMERANIAN - Awang Teja Satria (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Endocarditis is one of the causes of heart disease and as a major cause of congestive heart failure (CHF), namely a pathological condition due to the heart can not carry out its function to pump blood adequately in to sufficient the body's metabolic needs, including oxygen and nutrients. The clinical symptoms of endocarditis vary from mild to severe and often lead to death. This study aims to prove the existence of impaired heart function in a Pomeranian dog in determining the diagnosis of endocarditis through physical, hematological, X-ray and echocardiography/ultrasound. Reliability and accuracy in diagnosing endocarditis are important factors in therapeutic efforts that can improve clinical conditions and extend the life span of dogs. A 4-year-old male Pomeranian dog suspected of suffering from Endocarditis since 2 months ago, with clinical manifestations of dyspnea, cough, fever, pale and decreased or lost appetite. Physical examination of dogs followed by blood tests showed Leukocytosis (37.5 µL), Thrombocytosis (686 µL), Granulocytosis (30.3 µL) and Lymphocytosis (6.1 µL) which indicated inflammation or chronic infection. While on the results of the blood chemistry examination, an increase in Alkaline Phosphatase / ALP (115 цL) showed a dysfunction of non-specific organs such as the pancreas, liver, bone, kidney. Furthermore, the accuracy of diagnosis is done by X-ray examination in the left dorsal, right dorsal and dorsoventral positions. Ventrodorsal position is not recommended because of shortness of breath dog consideration. X-ray results showed Cardiomegaly which showed an enlargement of the right atrial area with a rounded heart apex, and vasodilation in the pulmonary arteries and veins. While on echocardiography/ultrasound examination showed tricuspidalis valve thickening and a bit slow closing, giving a tachycardia effect with the Right Ventricular / RV diameter ratio when diastole (1.30 cm) is greater than the Left Ventricel / LV diameter ratio (0.96 cm). Based on the results of ultrasound which is supported by the results of clinical examination, blood chemistry and X-ray, provides an interpretation of the diagnosis of Endocarditis so that treatment can be carried out appropriately and accurately.